(untitled) (Revista Latino-Americana de Enfermagem, 1999)
This article describes the tool used to collect data for nursing evaluation of patients with chronic pain patient in the League Against Pain of the University of São Paulo at Ribeirão Preto Faculty of Medicine, Brazil. The aim is to identify the patients' nursing care needs. The nursing diagnoses proposed by the North American Nursing Diagnosis Association (NANDA) were used to point out the patients' nursing care needs. The Human Response Patterns, in which the nursing diagnoses are classified by NANDA, were used as a framework to construct the tool. The way it is used by nursing undergraduate students, members of the League Against Pain, is also described.